Signal Enhancement of SPR Biosensor Detection by Using of Gold Nanoparticles for Human beta-2-Microglobulin as a Model Protein Biomarker - Mezentsev, Yu.V.; Gnedenko, O.V.; Ershov, P.V.; Ivanov, A.S. (Biomedical Chemistry: Research and Methods, 2018)
The highly sensitive method of surface plasmon resonance (SPR) detection of low concentrations of target proteins based on the biosensor signal enhancement by using gold nanoparticles (similar to “sandwich” assay type) is described. The commercial protein preparations of beta-2-microglobulin (B2M) as a model biomarker and polyclonal (Pab) and monoclonal antibodies (Mab) to B2M were used. It has been shown that this universal and reproducible method can be applied for SPR analysis of other protein biomarkers by analogy with the biomarker protein B2M. The present work is also focused on the experimental protocol description. The protocols of gold nanoparticles (GNP) synthesis, obtaining the conjugates of Pab/GNP and measuring their concentration, the protocol of Mab covalent immobilization on the optical chip CM5 of a biosensor and also SPR registration of molecular interactions Mab-biomarker and in the “sandwich” assay type Mab-biomarker-Pab or Mab-biomarker-Pab/GNP are considered in detail.